Academic stars and university rankings in higher education: impacts on policy and practice. Issue 1 (2nd January 2020) - Stack, Michelle
ABSTRACT: Drawing on the concepts of mediatisation and celebrification, this paper analyses how the Nobel Prize is used as a proxy of excellence by the 'Big Three' university rankers and top-ranked universities. Ranking advisories, university leadership at top-ranked institutions, and Nobel Prize adjudication committees are overwhelming from the same demographic: white men from the Global North. Who they deem 'world class' is overwhelmingly from the same demographic. Even though universities no longer have policies that keep out equity-seeking groups, the metrics used to determine world-classness re-entrench who is seen as a scholarly and administrative leader in higher education and what is considered world class knowledge. Drawing on social network analysis and multimedia critical discourse analysis, this paper argues that Nobel adjudication committees, ranking advisories and the leadership of top-ranked institutions form an echo chamber that conflates academic excellence with being white, male, wealthy, and famous. The paper concludes with the urgent need to address the cognitive dissonance of universities promoting spurious media-based metrics while at the same time claiming a commitment to equity policies and practices.